Identification of mycobacteria isolated at University Hospital of Santa Maria, Rio Grande do Sul, Brazil - Vanessa Albertina Agertt; Tanise Vendruscolo Dalmolin; Pauline Cordenonsi Bonez; Caren Rigon Mizdal; Jaciane Baggiotto Marques; Vanessa da Costa Flores; Adelinde Salla; Marli Matiko Anraku de Campos (Sociedade Brasileira de Patologia Clínica, 2013)
This study evaluated the prevalence of nontuberculous mycobacterium (NTM) in relation to the total number of cases of mycobacterial infections detected in patients admitted at the University Hospital of Santa Maria from 2008 to 2010. From the positive samples for the genus Mycobacterium, 67% belonged to the Mycobacterium tuberculosis complex (MTBC) and 33% of them were classified as NTM. This investigation aims to contribute to the epidemiology of mycobacterioses, inasmuch as patients infected by NTM require distinctive treatment and monitoring in comparison with those infected by MTBC.